Intracerebroventricular Enzyme Replacement Therapy in Patients with Neuropathic Form of Mucopolysaccharidosis Type II: to Help Practicing Physician - Nataliya V. Zhurkova; Nato D. Vashakmadze; Georgiy A. Karkashadze; Elena V. Kaytukova (Вопросы современной педиатрии)
Mucopolysaccharidosis type II (Hunter syndrome, MPS II) is a rare hereditary disease from the group of hereditary metabolic diseases. There are neuropathic and non-neuropathic forms of this disease. The neuropathic form is most common and leads to severe cognitive impairment and progressive damage of central nervous system. Nowadays, early diagnosis and timely initiation of pathogenetic therapy in patients with orphan diseases is the crucial problem of modern pediatrics. Intracerebroventricular administration of idursulfase beta is one of the promising treatment options in patients with neuropathic form of MPS II as it prevents severe complications development. The study of new pathogenetic therapy methods for rare hereditary diseases will help doctors of pediatric specialties to route patient correctly in timely manner to receive all the necessary treatment.